Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.